Efficacy of Isolated and Combined Application of Topical Metronidazole and Chlorhexidine in the Treatment of Periodontal Inflammation a Randomized Controlled Trial - Maryam Panhwar, Neha Manzar, Batool Bibi, Mahwash Malik Baloch, Tahera Ayub, Amna Rehman, (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: To evaluate the effectiveness of Metronidazole (MTZ) and Chlorhexidine (CHX) gels if used alone or in combination in the treatment of periodontal inflammation Materials and Methods: A Randomized clinical trial, was conducted at the Department of Periodontology, Liaquat University of Medical and Health Sciences, in which patient having moderate to severe periodontitis, assessed by using CPTIN community periodontal index, and bleeding index. Participants were randomly allocated to one of the three groups, Group A -CHX gel Group B – MTZ gel Group C - MTZ gel, and CHX gel both (MTZ –CHX). Furthermore, these indexes were assessed at the 4th, 8th and 12th weeks, and questions were recorded for any adverse effects. Data was analyzed using (SPSS) ANOVA– test used for comparison within groups and finally Repeated measure ANOVA-test was used for intergroup evaluation. Results: A significant improvement in the periodontal status and bleeding index was observed in all treatment groups from the treatment groups when compare baseline scores to all follow-up weeks, mean periodontal status of CHX (baseline:2.7776, 4th week:1.2463, 8th week:2.230, 12th week 0.848) MTZ (baseline: 2.548, 4th week:1.7120, 8th week:1.988, 12th week:1.109) CHX+MTZ (baseline: 2.333, 4th week 1.2432, 8th week 1.482, 12th week:0.524 with p-value 0.0001, However bleeding index showed significant results at the 12th week (CHX:0.825, MTZ:0.125, CHX+MTZ:0.124) with the p-value 0.005 Conclusion: Adjunctive use of topical gels showed significant improvements in clinical and numerical parameters in periodontitis. Keywords: Localized; Metronidazole, Chlorhexidine, Periodontium; inflammation.